Comparison of Personality Organization in People with Dark and Bright Personality Traits - Salman Nasab, Azad; Yusefi, Rahim; Yagubi, Hasan (Iranian Journal of Neurodevelopmental Disorders, 2024)
Purpose: The dual aspects of human personality, characterized by the dark and light triads, significantly influence various psychological and behavioral outcomes. The dark triad includes narcissism, Machiavellianism, and psychopathy, while the light triad comprises empathy, compassion, and altruism. This study aimed to compare the personality organization of individuals with dark and light personality traits, focusing on Kornberg’s dimensions: identity diffusion, primitive defenses, and reality testing. Methodology: This causal-comparative study included a sample of 232 students from Shahid Madani University of Azerbaijan, selected using purposive sampling. Participants completed questionnaires assessing dark and light personality traits and the Personality Organization Inventory. Data were analyzed using SPSS-25, employing descriptive statistics and multivariate analysis of variance (MANOVA) to compare the groups. Findings: Significant differences were found among individuals with dark traits, light traits, and normal individuals across all three dimensions of personality organization. Individuals with dark traits exhibited higher levels of primitive defenses (M = 28.25), greater identity diffusion (M = 25.75), and poorer reality testing (M = 49.93) compared to those with light traits (M = 24.30, M = 22.37, M = 38.81, respectively) and normal individuals (M = 26.23, M = 22.28, M = 41.87, respectively). Conclusion: The findings highlight that individual with dark traits have a more fragmented personality organization, characterized by maladaptive coping strategies and distorted reality perception, which contribute to their manipulative and antisocial behaviors. In contrast, individuals with light traits exhibit more cohesive personality organization, leading to prosocial and adaptive behaviors. These insights are crucial for developing targeted interventions to promote psychological well-being and improve organizational fit.